1977
DOI: 10.3758/bf03209189
|View full text |Cite
|
Sign up to set email alerts
|

Interference effects in tone memory

Abstract: Memory for a standard tone in comparison to a subsequent test tone was examined in three experiments with three intervening tones between the standard and test tones. In each trial, the intervening tones were presented from one of seven frequency range and distance from the standard tone conditions. Experiment 1 tone patterns were played at four different presentation rates, and the subjects judged whether the test was higher or lower than the standard. Memory interference effects caused by the different inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Cook’s work affirms the obvious intuition that more recent sonorities have a greater influence on key determination than sonorities from the distant past. This accords with experimental evidence showing that auditory memory is disrupted by the occurrence of subsequent sounds (Butler & Ward, 1988; Deutsch, 1972; Dewar, Cuddy, & Mewhort, 1977; Massaro, 1970a; Olsen & Hanson, 1977; Wickelgren, 1966)…”
Section: Introductionsupporting
confidence: 91%
“…Cook’s work affirms the obvious intuition that more recent sonorities have a greater influence on key determination than sonorities from the distant past. This accords with experimental evidence showing that auditory memory is disrupted by the occurrence of subsequent sounds (Butler & Ward, 1988; Deutsch, 1972; Dewar, Cuddy, & Mewhort, 1977; Massaro, 1970a; Olsen & Hanson, 1977; Wickelgren, 1966)…”
Section: Introductionsupporting
confidence: 91%
“…In this last condition, the interpolated tones formed very large intervals, and as a result, listeners were unable to make use of frameworks of pitch relationships to which the test tones could be anchored. Olson and Hanson (1977) also found that increased distances between the test and interpolated tones were associated with increased errors in pitch recognition (see also Deutsch & Boulanger, 1984).…”
Section: G Pitch Proximity and Pitch Memorymentioning
confidence: 85%
“…The interpolation of an extra tone during the retention interval produces a further decrement in performance (Wickelgren, 1966(Wickelgren, , 1969. When several tones are interpolated, recognition accuracy varies as a function of the pitch relationships between the tones to be compared and the intervening tones (Deutsch, 1975), and also varies as a function of the pitch relationships between successive tones of the interpolated sequence (Deutsch, 1972(Deutsch, , 1978Olson & Hanson, 1977). It has also been found that pitch recognition judgments can be substantially affected by the relational context in which the standard (S) and comparison (C) tones are placed, when simultaneous tones are used to provide such context.…”
mentioning
confidence: 99%